2020
DOI: 10.5539/jel.v9n1p119
|View full text |Cite
|
Sign up to set email alerts
|

Using Nearpod as a Tool to Promote Active Learning in Higher Education in a BYOD Learning Environment

Abstract: The present study aims to explore Nearpod as a tool to promote active learning in higher education. In this study, Nearpod is regarded as a tool that can be used to enhance teaching and learning for those lectures provided by male instructors to female students at Sharoura College of Science and Arts, Najran University. Hence, the Nearpod is integrated with video-conference learning system which is used as distance learning system to provide lectures by male lecturers to female students who study at a separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 21 publications
(32 reference statements)
7
52
0
8
Order By: Relevance
“…Institutional support was reported important to solve this minor problem. Hakami (2020) reported that female students at Sharoura College of Science and Arts of Najran University had favorable views of Nearpod (i.e., a web-based learning app.) when integrated with a video-conferencing system in a Bring Your Own Device (BYOD) learning environment.…”
Section: Summary Of Major Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Institutional support was reported important to solve this minor problem. Hakami (2020) reported that female students at Sharoura College of Science and Arts of Najran University had favorable views of Nearpod (i.e., a web-based learning app.) when integrated with a video-conferencing system in a Bring Your Own Device (BYOD) learning environment.…”
Section: Summary Of Major Resultsmentioning
confidence: 99%
“…The third study (Alshehri and Cumming, 2020) reported on a third e-learning tool (Mobile technologies) and the students' and teachers' perceptions of these in King Abdulaziz and King Khalid universities. The fourth study (Hakami, 2020) reported on a fourth e-learning tool (Nearpod) and the students' perspectives of it in Najran University.…”
Section: Rationale For Choosing the Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Hasil penelitian menunjukkan bahwa fitur-fitur dari Nearpod untuk mempresentasikan dan mengajukan pertanyaan (Real-Time Asesment) oleh siswa sebagai hal yang paling mendorong mereka untuk terlibat dalam kegiatan pembelajaran di kelas. Selain itu, cara kontrol materi Nearpod membantu pendidik dalam tugas pembelajaran (Hakami, 2020). Berdasarkan permasalahan di atas dan adanya beberapa teknologi yang dapat digunakan dalam PJJ secara gratis, maka perlu dilakukan pelatihan atau bimbingan teknis untuk guru-guru IPA terkait pemanfaatan perangkat lunak tersebut.…”
Section: Abstrakunclassified
“…More digital tools for active learning are published in Dexter et al ( 2020 ). Hakami ( 2020 ) shows that student engagement improved with Nearpod which is a digital tool that combines formative assessment and active learning in digital environments by using digital quizzes, polls, drawing, open ended questions. Dahdal ( 2020 ) shows how the use of WhatsApp promotes active learning and student engagement.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%